The Effect of Price, Brand Trust, and Brand Image on Smartphone Purchase Decisions - Sutria Kumala; Yasri Yasri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of price, brand trust, and brand image on smartphone purchasing decisions among college students. College students are young consumers with special characteristics, such as limited budget but have a high orientation towards trends, quality, and brand value. This study uses a quantitative approach with an associative design. A sample of 150 respondents was determined through a purposive sampling technique, namely active students who have used smartphones in the last six months. Data collection was carried out through a closed questionnaire with a five-point Likert scale. The instrument was tested through validity and reliability tests, and continued with testing classical assumptions such as normality, multicollinearity, and heteroscedasticity. Data analysis was carried out using multiple linear regression and the F test. The results showed that price, brand trust, and brand image had a significant effect on purchasing decisions, both partially and simultaneously. Among the three variables, brand image is the most dominant factor influencing purchasing decisions. This shows that the perception of a brand as a symbol of trends, lifestyle, and identity greatly influences college students in choosing a product, although they still consider the aspects of price and trust in quality